Photo-thermal nano particle, photo-thermal self-driven hydrophobic anti-icing coating and preparation method and application of photo-thermal self-driven hydrophobic anti-icing coating

By wrapping the silica shell on the surface of the nanomaterial and grafting silane groups, photothermal nanoparticles with high solar absorption and superhydrophobic properties are prepared. Combining resin and nanosilicon dioxide, existing hydrophobic anti-ice coatings are solved. The problems of low solar light absorption and poor oleophobic properties achieve multiple excellent performances of the coating.

CN119432141AInactive Publication Date: 2025-02-14INNOVATION CENTER OF YANGTZE RIVER DELTA ZHEJIANG UNIVERSITY

Patent Information

Application Number
CN202411571433.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing hydrophobic anti-ice coatings have low solar absorption and poor oleophobic properties, making it difficult to effectively prevent the formation of frost and the adhesion of pollutants.

Method used

By using nanomaterials as carriers, covering the silica shell on its surface, and grafting reactions through silane coupling agent, photothermal nanoparticles with high solar light absorption and superhydrophobic properties are prepared, combining resin and nanodioxide. Prepare photothermal self-driven hydrophobic anti-ice coatings with silicon and other components.

Benefits of technology

The coating has high solar absorption, superhydrophobic, oleophobic, hardness and wear resistance properties, effectively inhibiting the formation of frost, reducing the probability of icing, and improving the self-cleaning effect of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432141A_ABST
    Figure CN119432141A_ABST
Patent Text Reader

Abstract

The invention provides a photo-thermal nanoparticle, a photo-thermal self-driven hydrophobic anti-icing coating and a preparation method and application thereof, and belongs to the technical field of hydrophobic anti-icing materials. The invention provides a preparation method of photo-thermal nano-particles, which comprises the following steps: mixing a nano-material and tetraethoxysilane under an alkaline condition for hydrolysis, and coating the surface of the nano-material with a silicon dioxide shell to obtain coated nano-particles; and mixing the coated nanoparticles with a silane coupling agent, and carrying out a grafting reaction to obtain the photo-thermal nanoparticles. The preparation method comprises the following steps: by taking a nano material as a carrier, generating a silicon dioxide shell on the surface of the nano material through modification, and then modifying the silicon dioxide shell (carrying out grafting reaction), so that the silicon dioxide shell is grafted with a silane group, and the prepared photo-thermal nano particle has high sunlight absorptivity and super-hydrophobic and super-oleophobic characteristics. The photo-thermal self-driven hydrophobic anti-icing coating is prepared by using the photo-thermal nanoparticles as a main filler and coupling a high-hardness film-forming substance and a related auxiliary agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrophobic anti-icing materials, and in particular to a photothermal nanoparticle, a photothermal self-driven hydrophobic anti-icing coating, and a preparation method and application thereof. Background Art

[0002] Hydrophobic and anti-icing surfaces have great market application prospects due to their strong waterproof, anti-fouling, self-cleaning, anti-icing and anti-frost properties. Common application scenarios include power lines and communication towers, aircraft wings and fuselages, wind turbine blades, automotive industry, building roofs and walls, outdoor sports equipment, etc. Spraying hydrophobic and anti-icing coatings on the substrate surface is currently a more commonly used method for preparing hydrophobic and anti-icing surfaces. When applied, the process has the following advantages: 1. Simple coating preparation process: Compared with etching, chemical vapor deposition, anodizing and other methods to prepare super hydrophobic surfaces, the coating preparation process is simple, the construction is convenient and efficient, and it is suitable for large-area applications; 2. Wide applicability: Sprayed hydrophobic anti-icing coatings can be applied to substrates of various materials, including metal, glass, plastic, ceramic, etc., without being restricted by the type of substrate. At the same time, for surfaces with complex or irregular shapes, the sprayed hydrophobic anti-icing coating can be evenly covered to avoid dead corners and uneven problems; 3. Controllable thickness: The spray thickness can be controlled by the number of spraying times and spraying parameters to meet the needs of different application scenarios; 4. Convenient repair and maintenance: When the hydrophobic anti-icing surface is damaged, it can be repaired by spraying again, which is easy to operate and low cost.

[0003] The hydrophobic and anti-icing surface properties are mainly based on the properties of the coating. There have been many reports on the preparation of super-hydrophobic coatings. For example, the relevant technology discloses ultrasonically blending a resin binder with a solvent to obtain a resin mixed solution, dispersing carbon nanotubes and hydrophobic nano-silica in the resin mixed solution, and then adding a silane coupling agent to obtain a nanoparticle composite suspension, spraying the nanoparticle composite suspension onto the surface of the polished and cleaned pretreated substrate, and then drying and curing it to obtain a fluorine-free, wear-resistant, super-hydrophobic anti-icing coating. However, there are still problems of low solar absorption and poor oleophobic performance. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a photothermal nanoparticle, a photothermal self-driven hydrophobic anti-icing coating, and a preparation method and application thereof. The photothermal nanoparticle provided by the present invention has high solar light absorption rate and super hydrophobic and oleophobic properties.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing photothermal nanoparticles, comprising the following steps:

[0007] The nanomaterial and ethyl orthosilicate are mixed and hydrolyzed under alkaline conditions, and a silicon dioxide shell is coated on the surface of the nanomaterial to obtain coated nanoparticles;

[0008] The wrapped nanoparticles and a silane coupling agent are mixed to carry out a grafting reaction to obtain the photothermal nanoparticles.

[0009] Preferably, the mass ratio of the nano material to tetraethyl orthosilicate is 5-15:5-15.

[0010] Preferably, the mass ratio of the nano material to the silane coupling agent is 5-15:1-5.

[0011] Preferably, the silane coupling agent includes one or more of γ-methacryloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, 1H,1H,2H,2H-perfluorodecyltrimethoxysilane and 1H,1H,2H,2H-perfluorodecyltriethoxysilane.

[0012] The present invention also provides photothermal nanoparticles prepared by the preparation method described in the above technical solution. The photothermal nanoparticles use nanomaterials as carriers, and a silicon dioxide layer is wrapped on the surface of the carrier. The surface of the silicon dioxide layer is grafted with silane groups through chemical bonding.

[0013] The present invention also provides the application of the photothermal nanoparticles described in the above technical solution in the field of hydrophobic anti-icing.

[0014] The present invention also provides a photothermal self-driven hydrophobic anti-icing coating, comprising the following components in percentage by mass:

[0015] The above technical solution comprises 1-5% of photothermal nanoparticles, 2-8% of nano silicon dioxide, 10-20% of resin, 0.1-0.5% of leveling agent, 0.1-0.5% of defoaming agent, 1-5% of UV absorber and 70-80% of solvent.

[0016] Preferably, the resin is silicone resin and / or fluorocarbon resin.

[0017] Preferably, the particle size of the nano-silicon dioxide is 20 to 500 nm.

[0018] The present invention also provides the application of the photothermal self-driven hydrophobic anti-icing coating described in the above technical solution in the field of hydrophobic anti-icing coatings.

[0019] The invention provides a method for preparing photothermal nanoparticles, comprising the following steps: mixing nanomaterials and tetraethyl orthosilicate under alkaline conditions for hydrolysis, coating the surface of the nanomaterial with a silicon dioxide shell to obtain coated nanoparticles; mixing the coated nanoparticles with a silane coupling agent for grafting reaction to obtain the photothermal nanoparticles.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention uses nanomaterials as carriers, generates a silica shell on its surface through modification, and then modifies the silica shell (grafting reaction occurs) to graft silane groups to prepare photothermal nanoparticles with high solar light absorption rate and super hydrophobic and oleophobic properties. The photothermal nanoparticles are used as the main filler, and high-hardness film-forming substances (resins) are coupled with related additives that enhance the performance of the coating (including leveling agents, defoamers and UV absorbers) to prepare a photothermal self-driven hydrophobic anti-icing coating. The coating of the present invention is simple to apply and is suitable for various coating schemes such as spraying, brushing, and roller coating. The prepared coating has a high solar light absorption rate (≥95%, GB / T 2680-2021), super hydrophobic (contact angle ≥157°, rolling angle ≤10°), high hardness (≥3H), oleophobic (soybean oil contact angle ≥120°) and other excellent properties. The high solar light absorption rate of the photothermal nanoparticles ensures the photothermal conversion effect of the coating, converts light energy into heat energy, increases the surface temperature of the coating, and inhibits the formation of frost; the super hydrophobic properties of the photothermal nanoparticles and the micro-nano structure of the coating surface (formed by nano-silicon dioxide) make the coating super hydrophobic, and water droplets roll against the coating. The angle is low, it is easier to roll off, thereby reducing the probability of freezing. At the same time, the water droplets on the surface of the coating are spherical in shape with a high contact angle. The contact area between the water droplets and the coating surface is small, which can reduce the heat transfer efficiency and delay the freezing of the water droplets. The hydrophobic and oleophobic properties ensure that the coating can effectively prevent pollutants from penetrating and adhering to the coating surface, which can enhance the self-cleaning effect of the coating. The shell structure composed of the carrier of the photothermal nanoparticles - silica shell - silane groups, nano-silica and high-hardness film-forming materials ensure the high hardness and wear resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the structure of the photothermal self-driven hydrophobic anti-icing coating of the present invention. DETAILED DESCRIPTION

[0023] The present invention provides a method for preparing photothermal nanoparticles, comprising the following steps:

[0024] The nanomaterial and ethyl orthosilicate are mixed and hydrolyzed under alkaline conditions, and a silicon dioxide shell is coated on the surface of the nanomaterial to obtain coated nanoparticles;

[0025] The wrapped nanoparticles and a silane coupling agent are mixed to carry out a grafting reaction to obtain the photothermal nanoparticles.

[0026] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.

[0027] The invention mixes nano material and ethyl orthosilicate under alkaline conditions to carry out hydrolysis, and coats the surface of the nano material with a silicon dioxide shell to obtain coated nano particles.

[0028] In the present invention, the nanomaterial preferably includes one or more of halloysite nanotubes, nano titanium nitride, nano silicon carbide, carbon nanotubes and carbon black, and the nanomaterial is a carrier.

[0029] In the present invention, the particle size of the nanomaterial is preferably 20 to 500 nm, specifically 20, 200 or 500 nm, or a mixture of 20, 200 and 500 nm.

[0030] In the present invention, the mass ratio of the nanomaterial to tetraethyl orthosilicate is preferably 5-15:5-15, specifically 15:5, 15:10 or 15:15; silicon dioxide generated by hydrolysis of tetraethyl orthosilicate under alkaline conditions adheres to the surface of the nanomaterial, eventually forming a silicon dioxide shell.

[0031] In the present invention, the alkaline condition is preferably provided by an alkaline reagent, and the alkaline reagent is preferably an inorganic alkaline substance or an organic alkaline substance, and the inorganic alkaline substance is preferably ammonia water or sodium carbonate, and the organic alkaline substance is preferably sodium methyl silicate; the alkaline reagent promotes the hydrolysis of tetraethyl orthosilicate, and the -OR group in tetraethyl orthosilicate (Si-(OR)4) is replaced step by step by -OH in the alkaline environment, and the silanol (Si(OH)4) generated by hydrolysis is further dehydrated and condensed to form a silicon oxygen network (Si-O-Si), and finally after the reaction system is transformed from sol to gel, a layer of silica shell is generated on the surface of the nanomaterial. In the present invention, the concentration of the ammonia water is preferably 25% to 28%, and the concentration here refers to the percentage of the mass of ammonia in the ammonia water to the total mass of the solution.

[0032] In the present invention, the mass ratio of the nano material to the alkaline agent is preferably 5-15:1-5.

[0033] In the present invention, the hydrolysis is preferably carried out under the condition of a solvent, and the solvent is preferably a solvent with low surface tension, and more preferably includes one or more of ethanol, isopropanol, isobutanol and butyl acetate. The function of the solvent is to fully wet the surface of the nanomaterial, promote the uniform dispersion of the particles in the solution, prevent the agglomeration and sedimentation of the particles, and make the modification of the nanoparticles more complete. The solvent has low toxicity and biodegradability, and is safer for the environment and human health.

[0034] In the present invention, the mass ratio of the nano material to the silane coupling agent is preferably 5-15:1-5.

[0035] In the present invention, the silane coupling agent preferably includes one or more of γ-methacryloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, 1H,1H,2H,2H-perfluorodecyltrimethoxysilane and 1H,1H,2H,2H-perfluorodecyltriethoxysilane.

[0036] In the present invention, the hydrophobicity of the silica shell is improved by chemical bonding and surface modification with a silane coupling agent. The silane group (Si-OR) in the silane coupling agent can react with the hydroxyl group (Si-OH) on the surface of the silica, thereby being grafted on the surface of the silica shell. At the same time, the fluorine atoms and alkyl chains in the silane coupling agent are hydrophobic groups, which can significantly reduce the surface energy of the photothermal nanoparticles, so that the particles have good hydrophobicity.

[0037] In the present invention, the hydrolysis and grafting reactions are preferably carried out at room temperature under stirring conditions, and the rotation speeds of the hydrolysis and grafting reactions are independently 800-1200 rpm, specifically 800, 900, 1000, 1100 or 1200 rpm; the total time of the hydrolysis and grafting reactions is preferably 1-5 h, specifically 1, 2, 3, 4 or 5 h.

[0038] In a specific embodiment of the present invention, the nanomaterial, solvent, alkaline agent, tetraethyl orthosilicate and silane coupling agent are preferably mixed in sequence for reaction, and then centrifuged and dried to obtain the photothermal nanoparticles.

[0039] The present invention has no particular limitation on the specific parameters of the centrifugation and drying, and methods well known to those skilled in the art may be used.

[0040] The present invention also provides photothermal nanoparticles prepared by the preparation method described in the above technical solution. The photothermal nanoparticles use nanomaterials as carriers, and a silicon dioxide layer is wrapped on the surface of the carrier. The surface of the silicon dioxide layer is grafted with silane groups through chemical bonding.

[0041] In the present invention, the particle size of the photothermal nanoparticles is preferably 20 to 100 nm, specifically 20, 30, 40, 50, 60, 70, 80, 90 or 100 nm.

[0042] The present invention also provides the application of the photothermal nanoparticles described in the above technical solution in the field of hydrophobic anti-icing.

[0043] The present invention also provides a photothermal self-driven hydrophobic anti-icing coating, comprising the following components in percentage by mass:

[0044] The above technical solution comprises 1-5% of photothermal nanoparticles, 2-8% of nano silicon dioxide, 10-20% of resin, 0.1-0.5% of leveling agent, 0.1-0.5% of defoaming agent, 1-5% of UV absorber and 70-80% of solvent.

[0045] The mass percentage of photothermal nanoparticles in the photothermal self-driven hydrophobic anti-icing coating of the present invention is preferably 2-4%, specifically 2%, 3%, 4% or 5%; the photothermal nanoparticles are the main functional materials, which ensure the photothermal performance and super-hydrophobic performance of the coating. Excessive photothermal nanoparticles will lead to poor adhesion of the coating, excessive viscosity of the coating and other problems. Too few photothermal nanoparticles will lead to insufficient photothermal and hydrophobic effects of the coating.

[0046] The mass percentage of nano-silica in the photothermal self-driven hydrophobic anti-icing coating of the present invention is preferably 3-7%, specifically 2%, 3%, 4%, 5%, 6%, 7% or 8%; the nano-silica can form a micro-nano rough structure on the surface of the coating, further improving the hydrophobic performance of the coating, while enhancing the mechanical strength of the coating and the dispersibility of the coating. Too much nano-silica will result in poor adhesion of the coating and too high viscosity, while too little will result in insufficient micro-nano structure on the surface of the coating and poor hydrophobic performance.

[0047] In the present invention, the particle size of the nano-silicon dioxide is preferably 20 to 500 nm, more preferably 100 to 300 nm.

[0048] The mass percentage of resin in the photothermal self-driven hydrophobic anti-icing coating of the present invention is preferably 12-18%, specifically 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%. Resin is the main functional component for film formation of the coating. If the proportion of resin is too low, the film-forming effect of the coating is poor and the adhesion of the coating is insufficient. If the proportion of resin is too high, the photothermal and hydrophobic effects of the coating are poor.

[0049] In the present invention, the resin is preferably a silicone resin and / or a fluorocarbon resin. The resin is the main resin of the coating and provides a film-forming carrier. The silicone resin preferably includes one or more of a reactive methyl silicone resin, a one-component modified silicone resin and a methylphenyl silicone resin. The fluorocarbon resin preferably includes a solvent-based tetrafluorocarbon coating resin or a tetrafluoroethylene / vinyl monomer copolymer resin.

[0050] The mass percentage of the leveling agent in the photothermal self-driven hydrophobic anti-icing coating of the present invention is preferably 0.2-0.4%, specifically 0.1%, 0.2%, 0.3%, 0.4% or 0.5%. An appropriate amount of leveling agent can help the coating have a better leveling effect and avoid leveling defects. Adding too much will lead to prolonged leveling time.

[0051] In the present invention, the leveling agent preferably includes one or more of polyether-modified methyl alkyl polysiloxane, polyether-modified polydimethyl siloxane and polymethyl alkyl siloxane.

[0052] The mass percentage of the defoaming agent in the photothermal self-driven hydrophobic anti-icing coating of the present invention is preferably 0.2-0.4%, specifically 0.1%, 0.2%, 0.3%, 0.4% or 0.5%. An appropriate amount of defoaming agent can inhibit the generation of foam. Excessive use will lead to defects such as shrinkage holes and fish eyes.

[0053] In the present invention, the defoaming agent preferably includes one or more of polyether-modified silicon, higher alcohol defoaming agent and polysiloxane.

[0054] The mass percentage of the UV absorber in the photothermal self-driven hydrophobic anti-icing coating of the present invention is preferably 2-4%, specifically 2%, 3%, 4% or 5%. An appropriate amount of UV absorber can prevent the coating from undergoing photophysical and photochemical decomposition caused by ultraviolet rays, thereby increasing weather resistance. Adding too much will increase costs.

[0055] In the present invention, the UV absorber preferably includes one or more of benzophenone-based UV absorbers, benzotriazole-based UV absorbers, and o-hydroxyphenyltriazine-based UV absorbers.

[0056] The mass percentage of the solvent in the photothermal self-driven hydrophobic anti-icing coating of the present invention is preferably 72-78%, specifically 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79% or 80%. The function of the solvent is to control the fluidity of the coating. If the solvent is too little, the cost of the coating is high, the fluidity is poor, and the volatilization of the solvent will lead to curing. If the solvent is too much, the coating performance is poor.

[0057] In the present invention, the solvent preferably includes one or more of ethanol, isopropanol, isobutanol and butyl acetate.

[0058] The present invention has no special limitation on the preparation method of the photothermal self-driven hydrophobic anti-icing coating, and can be prepared in a manner familiar to those skilled in the art, such as mixing the components, stirring and dispersing at 1000-1500 rpm (specifically 1000, 1100, 1200, 1300, 1400 or 1500 rpm) for 10 minutes, filtering, and storing in a sealed light-proof container to obtain the photothermal self-driven hydrophobic anti-icing coating.

[0059] The present invention also provides the application of the photothermal self-driven hydrophobic anti-icing coating described in the above technical solution in the field of hydrophobic anti-icing coatings.

[0060] The present invention also provides a photothermal self-driven hydrophobic anti-icing coating, which is prepared by a method comprising the following steps: coating the photothermal self-driven hydrophobic anti-icing coating on the surface of a substrate and then curing it to form a photothermal layer, namely the photothermal self-driven hydrophobic anti-icing coating.

[0061] In the present invention, the material of the substrate is preferably aluminum, acrylonitrile / butadiene / styrene copolymer board (ABS board) or polyethylene terephthalate (PET) film.

[0062] The present invention has no particular limitation on the specific parameters of the curing, and methods well known to those skilled in the art may be used.

[0063] Figure 1 It is a schematic diagram of the structure of the photothermal self-driven hydrophobic anti-icing coating of the present invention.

[0064] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0065] The raw materials used in the embodiments of the present invention are:

[0066] The organic silicone resin is a reactive methyl organic silicone resin; the fluorocarbon resin is a solvent-based tetrafluorocarbon coating resin; the leveling agent is a polyether-modified polydimethylsiloxane; the defoaming agent is a high-carbon alcohol defoaming agent; and the UV absorber is a benzophenone-based UV absorber.

[0067] The test standard for hardness in the present invention is: GB / T 6739-2022 Paint and varnish pencil method for determining paint film hardness.

[0068] Example 1

[0069] 8 kg of carbon nanotubes, 80 kg of ethanol, 4 kg of ammonia water (concentration of 25%), 8 kg of ethyl orthosilicate, and 3 kg of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane were mixed in sequence, mechanically stirred at 1000 rpm for 2 hours, and centrifuged and dried to obtain photothermal nanoparticles.

[0070] 3kg of photothermal nanoparticles, 6kg of 100nm silica, 75kg of ethanol, 15kg of silicone resin, 0.3kg of leveling agent, 0.3kg of defoaming agent, and 3kg of UV absorber were mixed in sequence, mechanically stirred at 1000rpm for 15min, filtered and sprayed on an aluminum plate. After the coating was cured at room temperature, the surface characteristics of the coating were 96% solar light absorption rate, 157.8° hydrophobic angle, 4.3° water rolling angle, 135° soybean oil contact angle, and 4H hardness.

[0071] Example 2

[0072] 8 kg of carbon black, 80 kg of ethanol, 1 kg of sodium methyl silicate, 8 kg of ethyl orthosilicate, and 3 kg of 1H, 1H, 2H, 2H-perfluorodecyltrimethoxysilane were mixed in sequence, mechanically stirred at 1000 rpm for 2 h, and centrifuged and dried to obtain photothermal nanoparticles.

[0073] 4kg of photothermal nanoparticles, 5kg of 20nm silica, 75kg of ethanol, 15kg of fluorocarbon resin, 0.3kg of leveling agent, 0.3kg of defoaming agent, and 3kg of UV absorber were mixed in sequence, mechanically stirred at 1000rpm for 15min, filtered and sprayed on an aluminum plate. After the coating was cured at room temperature, the surface characteristics of the coating were 97% solar light absorption rate, 152.8° hydrophobic angle, 6.0° water rolling angle, 120° soybean oil contact angle, and 3H hardness.

[0074] Example 3

[0075] 8 kg of halloysite nanotubes, 80 kg of ethanol, 3 kg of ammonia water (concentration of 25%), 8 kg of ethyl orthosilicate, and 3 kg of 1H, 1H, 2H, 2H-perfluorodecyltrimethoxysilane were mixed in sequence, mechanically stirred at 1000 rpm for 2 h, and centrifuged to obtain photothermal nanoparticles.

[0076] 2kg of photothermal nanoparticles, 6kg of 100nm silica, 75kg of ethanol, 15kg of silicone resin, 0.3kg of leveling agent, 0.3kg of defoaming agent, and 3kg of UV absorber were mixed in sequence, mechanically stirred at 1000rpm for 15min, filtered and sprayed on an aluminum plate. After the coating was cured at room temperature, the surface characteristics of the coating were 95% solar light absorption rate, 153.0° hydrophobic angle, 5.5° water rolling angle, 120° soybean oil contact angle, and 5H hardness.

[0077] Example 4

[0078] 8 kg of silicon carbide, 80 kg of ethanol, 1 kg of sodium methyl silicate, 8 kg of ethyl orthosilicate, and 3 kg of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane were mixed in sequence, mechanically stirred at 1000 rpm for 2 h, and centrifuged and dried to obtain photothermal nanoparticles.

[0079] 2kg of photothermal nanoparticles, 6kg of 100nm silica, 75kg of ethanol, 15kg of silicone resin, 0.3kg of leveling agent, 0.3kg of defoaming agent, and 3kg of UV absorber were mixed in sequence, mechanically stirred at 1000rpm for 15min, filtered and sprayed on an aluminum plate. After the coating was cured at room temperature, the surface characteristics of the coating were 96% solar light absorption rate, 152.0° hydrophobic angle, 6.0° water rolling angle, 120° soybean oil contact angle, and 4H hardness.

[0080] Example 5

[0081] 8 kg of carbon nanotubes, 80 kg of ethanol, 4 kg of ammonia water (concentration of 25%), 8 kg of tetraethyl orthosilicate, and 5 kg of γ-methacryloxypropyltrimethoxysilane were mixed in sequence, mechanically stirred at 1000 rpm for 2 hours, and centrifuged and dried to obtain photothermal nanoparticles.

[0082] 2kg of photothermal nanoparticles, 6kg of 100nm silica, 75kg of isopropanol, 15kg of silicone resin, 0.3kg of leveling agent, 0.3kg of defoaming agent, and 3kg of UV absorber were mixed in sequence, mechanically stirred at 1000rpm for 15min, filtered and sprayed on an aluminum plate. After the coating was cured at room temperature, the surface characteristics of the coating were 95% solar light absorption rate, 155.0° hydrophobic angle, 6.0° water rolling angle, 120° soybean oil contact angle, and 3H hardness.

[0083] Example 6

[0084] 8 kg of carbon nanotubes, 80 kg of ethanol, 4 kg of ammonia water (concentration of 25%), 8 kg of ethyl orthosilicate, and 5 kg of γ-aminopropyltriethoxysilane were mixed in sequence, mechanically stirred at 1000 rpm for 2 hours, and centrifuged and dried to obtain photothermal nanoparticles.

[0085] 2kg of photothermal nanoparticles, 6kg of 100nm silica, 75kg of butyl acetate, 15kg of silicone resin, 0.3kg of leveling agent, 0.3kg of defoaming agent, and 3kg of UV absorber were mixed in sequence, mechanically stirred at 1000rpm for 15min, filtered and sprayed on an aluminum plate. After the coating was cured at room temperature, the surface characteristics of the coating were 95% solar light absorption rate, 153.0° hydrophobic angle, 6.0° water rolling angle, 120° soybean oil contact angle, and 3H hardness.

[0086] Comparative Example

[0087] 8 kg of carbon nanotubes, 80 kg of ethanol, and 8 kg of 100 nm silicon dioxide were sequentially mixed, mechanically stirred at 1000 rpm for 2 h, and centrifuged and dried to obtain a nanoparticle complex.

[0088] 2kg of nanoparticle composite, 6kg of 100nm silica, 75kg of butyl acetate, 15kg of silicone resin, 0.3kg of leveling agent, 0.3kg of defoaming agent, and 3kg of UV absorber were mixed in sequence, mechanically stirred at 1000rpm for 15min, filtered and sprayed on an aluminum plate. After the coating was cured at room temperature, the surface characteristics of the coating were 95% solar light absorptivity, 100.0° hydrophobic angle, 20.0° water rolling angle, 70.0° soybean oil contact angle, and 3H hardness.

[0089] In summary, the coating prepared by the present invention is easy to apply and can be sprayed or rolled indoors or outdoors. Various functional coatings have been widely used, the market is relatively mature, and the process cost is low.

[0090] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing photothermal nanoparticles, characterized in that: The following steps are involved: The nanomaterial and ethyl orthosilicate are mixed and hydrolyzed under alkaline conditions, and a silicon dioxide shell is coated on the surface of the nanomaterial to obtain coated nanoparticles; The wrapped nanoparticles and a silane coupling agent are mixed to carry out a grafting reaction to obtain the photothermal nanoparticles.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the nano material to tetraethyl orthosilicate is 5-15:5-15.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the nano material to the silane coupling agent is 5-15:1-5.

4. The preparation method according to claim 1 or 3, characterized in that: The silane coupling agent includes one or more of γ-methacryloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, 1H,1H,2H,2H-perfluorodecyltrimethoxysilane and 1H,1H,2H,2H-perfluorodecyltriethoxysilane.

5. The photothermal nanoparticles prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The photothermal nanoparticles use nanomaterials as carriers, and a silicon dioxide layer is wrapped on the surface of the carrier. The surface of the silicon dioxide layer is grafted with silane groups through chemical bonding.

6. Use of the photothermal nanoparticles according to claim 5 in the field of hydrophobic anti-icing.

7. A photothermal self-driven hydrophobic anti-icing coating, characterized in that: The following components are included in mass percentage: 1-5% of the photothermal nanoparticles as claimed in claim 5, 2-8% of nano-silicon dioxide, 10-20% of resin, 0.1-0.5% of leveling agent, 0.1-0.5% of defoaming agent, 1-5% of UV absorber and 70-80% of solvent.

8. The photothermal self-driven hydrophobic anti-icing coating according to claim 7, characterized in that: The resin is silicone resin and / or fluorocarbon resin.

9. The photothermal self-driven hydrophobic anti-icing coating according to claim 7, characterized in that: The particle size of the nano silicon dioxide is 20 to 500 nm.

10. Application of the photothermal self-driven hydrophobic anti-icing coating according to any one of claims 7 to 9 in the field of hydrophobic anti-icing coatings.

Citation Information

Patent Citations

  • Super-hydrophobic coating material with photo-thermal and sound absorption functions and preparation method thereof

    CN115232507A

  • Photo-thermal hydrophobic coating as well as preparation method and application thereof

    CN117126599A

  • Nano photo-thermal hydrophobic material as well as preparation method and application thereof

    CN117304728A

Cited By

  • Anti-photooxidation nano material as well as preparation method and application thereof

    CN121045649A